(untitled) (Journal of Environmental Science and Natural Resources, 2015)
Daily precipitation data of 33 stations were analyzed to know the Standardized Precipitation Index (SPI). Both spatial and temporal SPI were analyzed. Inverse Distance Weighting (IDW) technique was used to map the spatial SPI with a decadal change. From 1983 to 2013, four maps showed the decadal changes of SPI over Bangladesh. 1993 was a dry year in the regarding time period. Station based trends were analyzed for Dhaka, Srimongol, Khulna, Coxs bazaar and Rangpur as preventative for five regions in Bangladesh. Dryness is increasing over Northern and Central regions whereas wetness is increasing over Southwestern, Northern and eastern region in Bangladesh. DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22220 Environ. Sci. & Natural Resources, 7(2): 127-131 2014